Management Waste in The Public Service Area of The Southern Konawe Hospital - Lia Amelia; Erwin Azizi Jayadiparaja DM; Ridwan Adi Surya (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2018)
Waste from such hospital activity is likely to result in pathogenic microorganisms and toxic chemicals that cause infection and may spread to hospital environments due to inadequate health care techniques, errors in the treatment of contaminated materials and equipment, and the provision and maintenance of sanitary facilities still not good, can cause the occurrence of transmission of diseases originating from waste and declining aesthetic value. Therefore, to improve the quality of hospital services, the need for proper waste management and in accordance with established procedures. This study aims to analyze the waste management in the Regional Public Service Agency of South Konawe District Hospital.The type of this research is quantitative descriptive research. population in this research is all officer in charge of managing waste from start of room until to final disposal which amounted to 25 people. In this study using population research because the subject amounted to 25 people. The analysis used in this study uses descriptive analysis.The results show that the problem that exists on the input aspect is the head of the sanitation installation is not a minimal Diploma Kesling. But the Nutrition Diploma. Officers sent for training are only ambulance coordinator and IPRS Coordinator while management staff never participate in specific training. In the input aspect, the budget for limba management is carried out efficiency so that there is still need from the unfulfilled waste management. In the process aspect, the problem related to the waste management process itself starts from the transportation process where the officers rarely use personal protective equipment, there is no special lane, the garbage is collected for several days to be burned, also the burning that is accommodated to wait for the third party to carry the transportation.Expected To the South Konawe Hospital, it is necessary to consider following the Decree of the Minister of Health of the Republic of Indonesia Number 1204 / MENKES / SK / X / 2004 on the head of the sanitation installation is a minimum of Diploma 3 Environmental Health Keywords : Hospital Waste Management, Input, Output; Process